Cardiopulmonary resuscitation in pediatric patients under palliative home care – A multicenter retrospective study - Schneck, Emmanuel; Janßen, Gisela; Vaillant, Vera; Voelker, Thomas; Dechert, Oliver; Trocan, Laura; Schmitz, Lioba; Rohde, Marius; Sander, Michael; Hauch, Holger; Justus Liebig University Giessen (My University, 2023)
Introduction: Patients under palliative home care have special needs for their end-of-life support, which in general does not automatically include cardiopulmonary resuscitation. However, emergency medical services (EMS) respond to emergencies in children under palliative care that lead to cardiopulmonary resuscitation. To understand the underlying steps of decision-making, this retrospective, cross-sectional, multicenter study aimed to analyze pediatric patients under palliative home care who had been resuscitated. Methods: This study included patients from three spezialized pediatric palliative home care (SHPC) teams. The primary study parameters were the prevalence of cardiopulmonary resuscitation and the decision-making for carrying out pediatric advanced life support (PALS). Further analyses included the causes of cardiac arrest, the type of CPR (basic life support, advanced life support), the patient´s outcome, and involvement of the SHPC in the resuscitation. Descriptive statistical analysis was performed. Results: In total, 880 pediatric patients under palliative home care were included over 8.5 years, of which 17 patients were resuscitated once and two patients twice (overall, 19 events with CPR, 21.6 per 1,000 cases). In 10 of the 19 incidents (52.6%), cardiac arrest occurred suddenly without being predictable. The causes of cardiac arrest varied widely. PALS was performed in 78.9% of the cases by EMS teams. In 12 of 19 events (63.2%) resuscitation was performed on explicit wish of the parents. However, from a medical point of view, only four resuscitation attempts were reasonable. In total 7 of 17 (41.2%) patients survived cardiac arrest with a comparable quality of life. Discussion: Overall, resuscitation attempts were rare events in children under home palliative therapy, but if they occur, EMS are often the primary caregivers. Most resuscitation attempts occurred on explicit wish of the parents independently of the meaningfulness of the medical procedure. Despite the presence of a life-limiting disease, survival with a similar quality was achieved in one third of all resuscitated patients. This study indicates that EMS should be trained for advanced life support in children under home palliative therapy and SHPC should address the scenario of cardiac arrest also in early stages of palliative treatment. These results underline that advance care planning for these children is urgently needed.
Keywords: emergency medial services; ethics; CPR; advanced pediatric life support; rare diseases; chronic illness; end-of-life; palliative home care; ddc:610